The convergence of regenerative medicine and rehabilitation: federal perspectives. (December 2018) - Rose, L.; Wolf, E.; Brindle, T.; Cernich, A.; Dean, W.; Dearth, C.; Grimm, M.; Kusiak, A.; Nitkin, R.; Potter, K.; Randolph, B.; Wang, F.; et al.
Abstract Regenerative rehabilitation is the synergistic integration of principles and approaches from the regenerative medicine and rehabilitation fields, with the goal of optimizing form and function as well as patient independence. Regenerative medicine approaches for repairing or replacing damaged tissue or whole organs vary from utilizing cells (e.g., stem cells), to biologics (e.g., growth factors), to approaches using biomaterials and scaffolds, to any combination of these. While regenerative medicine offers tremendous clinical promise, regenerative rehabilitation offers the opportunity to positively influence regenerative medicine by inclusion of principles from rehabilitation sciences. Regenerative medicine by itself may not be sufficient to ensure successful translation into improving the function of those in the most need. Conversely, with a better understanding of regenerative medicine principals, rehabilitation researchers can better tailor rehabilitation efforts to accommodate and maximize the potential of regenerative approaches. Regenerative rehabilitative strategies can include activity-mediated plasticity, exercise dosing, electrical stimulation, and nutritional enhancers. Critical barriers in translating regenerative medicine techniques into humans may be difficult to overcome if preclinical studies do not consider outcomes that typically fall in the rehabilitation research domain, such as function, range of motion, sensation, and pain. The authors believe that encouraging clinicians and researchers from multiple disciplines to work collaboratively and synergistically will maximize restoration of function and quality of life for disabled and/or injured patients, including U.S. Veterans and Military Service Members (MSMs). Federal Government agencies have been investing in research and clinical care efforts focused on regenerative medicine (NIH, NSF, VA, and DoD), rehabilitation sciences (VA, NIH, NSF, DoD) and, more recently, regenerative rehabilitation (NIH and VA). As science advances and technology matures, researchers need to consider the integrative approach of regenerative rehabilitation to maximize the outcome to fully restore the function of patients.